Anemia: An Updated Review for Healthcare Professionals - Mutlaq, Hamoud Shukhayr; ALOTAIBI , KHALID ABDULLAH THAWAB; HUSAYKAN, IBRAHEM MOHSEN; Alotaibi, Sattam Shaleh Falah; Alotaibi, Fahad Hussain Hmaid; Alotibi , Faten Abdullah Abdulmihsen; Alotaibi , Eid Sunitan Eid; Abualssayl, Abdullah Ahmed; MUBARAK , ALDOSARI, MOHAMMED; Almutairi, Mohammed Hamdan; BINNWEJIM , MOHAMMED SALEH; Khabrani, Magbool Awaji Ali (Journal of Ecohumanism, 2024)
Background: Anemia is a prevalent condition marked by a reduction in red blood cells, leading to diminished oxygen transport. It is not a standalone diagnosis but a symptom of various underlying health issues. Symptoms typically arise when hemoglobin levels drop below 7.0 g/dL, including fatigue, pallor, and dyspnea. Aim: This review aims to provide an updated understanding of anemia's etiology, pathophysiology, epidemiology, and clinical management for healthcare professionals. Methods: A comprehensive literature review was conducted, focusing on the classification of anemia into hypoproliferative and hyperproliferative forms based on reticulocyte counts. Various subtypes were examined, including microcytic, normocytic, and macrocytic anemias, along with their associated causes and mechanisms. Results: Anemia affects approximately one-third of the global population, with varying prevalence based on demographics such as age, sex, and race. Iron deficiency anemia is particularly common among women of reproductive age. The pathophysiology involves either increased red blood cell destruction or impaired erythropoiesis. Clinical evaluation through history-taking and physical examination is crucial for diagnosing the underlying causes. Conclusion: Anemia presents a complex interplay of factors requiring targeted diagnostic and therapeutic approaches. Understanding its multifaceted nature is essential for effective management and improving patient outcomes.